Pengaruh Disiplin Kerja, Tingkat Absensi Dan Pengalaman Kerja Terhadap Produktivitas Kerja (Kasus pada Perusahaan Batik Brotoseno Sragen) - Harista, Rendra Fani, Drs.Sri Padmantyo (2016)
Research conducted by the Company Batik Sragen Brotoseno order to determine the work discipline, absenteeism, work experience on employee productivity. The method used by the population are employees of the Company Batik Sragen Brotoseno. The sampling technique using a simple way (convenience sampling) that anyone who met the Company's employees Brotoseno Batik Sragen. The analytical tool used: Test Instruments (Test Reliability, Validity), Classical Assumptions (Normality Test, Multicollinearity and Test heterocedastity), Multiple Regression Analysis, Test F, Test t-test and coefficient of determination (R2 ). The results of the analysis can be obtained:The t-test showed that the variables of Work Discipline , Attendance and Work Experience Levels no effect on Work Productivity individually. Test F shows that the variable Work Discipline, Attendance and Work Experience Levels significantly affect satisfaction Work Productivity together